Deep Inferior Epigastric Perforator Flap Breast Reconstruction in Patients With or Without Previous Abdominal Surgery: A Systemic Review and Meta-analysis - Gauthier Zinner, MS; Jérôme Martineau, MD; Carlo M. Oranges, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. The deep inferior epigastric perforator (DIEP) flap is now considered the gold standard for autologous breast reconstructions (BRs). Previous abdominal surgery (PAS) is considered to be a potential contraindication to abdominal-based BR. This systematic review and meta-analysis aim to evaluate the impact of PAS following a DIEP flap BR comparing patients with or without PAS. Methods:. A systematic review of the literature and comparative meta-analysis were performed to assess the differences in abdominal donor-site and flap complication rates between patients with or without PAS. Only comparative studies that reported on postoperative complications following DIEP flap BR were included. Odds ratios and 95% confidence intervals were calculated using a random-effects model. Results:. Nine studies were included, representing 2440 patients with or without PAS corresponding to 3082 DIEP flap BR. There were no differences across groups in flap-related complication rates. However, PAS was associated with an increase in the overall rate of abdominal complications (odds ratio = 1.92; 95% confidence interval = 1.41–2.62; P < 0.0001). Conclusions:. PAS is not a contraindication to DIEP flap BR, and no increase in the flap complication rate has been found in association with PAS. However, our study shows that PAS is associated with a higher overall abdominal complication rate at the donor site.